(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper aims to derive coefficient conditions, inclusion relations, and the starlikeness condition for a specific subclass of analytic functions in the open unit disc. Additionally, it establishes the necessary and sufficient conditions for the Pascal and Poisson distributions to belong to this subclass.